Effects of Labisia pumila on bone turnover markers and OPG/RANKL system in a rat model of post-menopausal osteoporosis. (August 2018) - Nurdiana, Nurdiana; Mariati, Nelly; Noorhamdani, Noorhamdani; Setiawan, Bambang; Budhiparama, Nicolaas; Noor, Zairin
Summary: The loss of bone mass due to the increasing age in women is caused by the decline in ovarian function, known as osteoporosis. Numerous studies have evaluated the benefits of Labisia pumila, but not investigated the OPG/RANKL system. The purpose of the present study was to analyze the effects of L. pumila extract on bone turnover markers and OPG/RANKL system in ovariectomized rats. Totally, twenty-five female Wistar rats were divided into five tgroups (n = 5), including the control group, ovariectomized group, ovariectomized group treated with L. pumila extract of various doses (10 mg/kg; 20 mg/kg and 40 mg/kg). L. pumila extract was administered daily for 8 weeks. Serum levels of osteocalcin, urine levels of deoxypiridinoline, serum levels of OPG and RANKL were analyzed by means of ELISA technique. Serum levels of deoxypiridinoline and urine levels of osteocalcin were significantly higher in the ovariectomized group than those of the control group ( p  < 0.05). All doses of L. pumila significantly reduced serum levels of osteocalcin compared to the ovariectomized group, reaching the levels comparable to those of the control group ( p  < 0.05). Only the highest dose of L. pumila significantly increased the levels of deoxypiridinoline relative to the ovariectomized and control groups ( p  < 0.05). The levels of OPG and RANKL and the ratio of OPG/RANKL did not differ significantly among the treatment groups ( p  > 0.05). In conclusion, the ethanol extract of L. pumila normalized osteoblastic bone formation, but could not prevent collagen degradation in bone in a rat model of post-menopausal osteoporosis. Graphical abstract: Highlights: Osteoporosis rats received Labisia pumila . Deoxypiridinoline significantly increased in OVX. Osteocalcin significantly higher in the OVX. All doses of L. pumila significantly reduced osteocalcin and deoxypiridinoline. OPG and RANKL and the ratio of OPG/RANKL did not differ significantly.